Vibrio parahaemolyticus: Basic Techniques for Growth, Genetic Manipulation, and Analysis of Virulence Factors. Issue 1 (7th December 2020) - Chimalapati, Suneeta; Lafrance, Alexander E.; Chen, Luming; Orth, Kim
Abstract: Vibrio parahaemolyticus is a Gram‐negative, halophilic bacterium and opportunistic pathogen of humans and shrimp. Investigating the mechanisms of V. parahaemolyticus infection and the multifarious virulence factors it employs requires procedures for bacterial culture, genetic manipulation, and analysis of virulence phenotypes. Detailed protocols for growth assessment, generation of mutants, and phenotype assessment are included in this article. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Assessment of growth of V. parahaemolyticus Alternate Protocol 1 : Assessment of growth of V. parahaemolyticus using a plate reader Basic Protocol 2 : Swimming/swarming motility assay Basic Protocol 3 : Genetic manipulation Alternate Protocol 2 : Natural transformation Basic Protocol 4 : Secretion assay and sample preparation for mass spectrometry analysis Basic Protocol 5 : Invasion assay (gentamicin protection assay) Basic Protocol 6 : Immunofluorescence detection of intracellular V. parahaemolyticus Basic Protocol 7 : Cytotoxicity assay for T3SS2